Livelihood experiences and adherence to HIV antiretroviral therapy among participants in a food assistance pilot in Bolivia: a qualitative study. - Kartika Palar (Public Library of Science (PLoS), 2013)
Introduction Health and development organizations increasingly promote livelihood interventions to improve health and economic outcomes for people living with HIV (PLHIV) receiving treatment with antiretroviral therapy (ART). In-depth understanding about how PLHIV make labor decisions in the context of treatment for HIV - and treatment decisions in the context of their livelihoods - is essential to guiding intervention design and developing hypotheses for future research on livelihoods and ART. However, few studies have explored the perspectives of PLHIV regarding integration of livelihoods and ART in urban, resource-limited settings. Methods Qualitative interviews explored the livelihood experiences of food insecure ART patients in four Bolivian cities (n = 211). Topics included work-related barriers to ART adherence, HIV-related barriers to work, and economic coping mechanisms. Themes were identified using content coding procedures, with two coders to maximize reliability. Results Participants reported complex economic lives often characterized by multiple economic activities, including both formal and informal labor. They struggled to manage ART treatment and livelihoods simultaneously, and faced a range of interpersonal and structural barriers. In particular, lack of HIV status disclosure, stigma, and discrimination were highly salient issues for study participants and likely to be unique to people with HIV, leading to conflict around requesting time off for clinic visits, resentment from co-workers about time off, and difficulties adhering to medication schedules. In addition, health system issues such as limited clinic hours or drug shortages exacerbated the struggle to balance economic activities with HIV treatment adherence. Conclusions Improved policy-level efforts to enforce existing anti-discrimination laws, reduce HIV-related stigma, and expand health services accessibility could mitigate many of the barriers discussed by our participants, improve adherence, and reduce the need for livelihoods interventions.